Coefficient of Structural Concordance and an Example of its Application: Labour Productivity and Wages in Slovenia - Verbič, Miroslav; Kuzmin, Franc (Panoeconomicus, 2009)
The article presents the underlying principles, derivation and properties of a simple descriptive measure of concordance between two analogous rank structures that we call the coefficient of structural concordance. It is based upon the idea of Kendall’s coefficient of concordance, which we extend to two rank structures. As the coefficient of structural concordance is a pure intergroup measure of concordance, it is designed to complement the Kendall’s intragroup coefficient of concordance. We apply this descriptive measure by exploring the relationship between wages and labour productivity in Slovenia for the period 1998–2007. We are able to confirm the hypothesis of high concordance between wages and labour productivity, which indicates a stimulative role of wages in production of market traded goods and services.Key words: Coefficient of structural concordance, Kendall’s coefficient of concordance, Labour productivity, Slovenia, Value added per employee, Wages.JEL: C10, C14, D24, J30.